CMOS high density electrical impedance biosensor array for tumor cell detection - Chandran, Jegatha (2012)
We present a high-throughput label-free electrical-impedance spectroscopy (EIS) platform composed of a 96 × 96 microelectrode array for counting and analysis of breast tumor cells (MCF-7). These Auelectrodes are densely packed within a 3.5 mm × 3.5 mm interrogation region. Each Au-electrode has an edge-length of 25 μm designed to detect single tumor cell by electrical impedance spectroscopy. The detected signal is read out via an integrated circuit (IC) of addressable electrode-selection-switch array manufactured with 0.18μm CMOS technology. The independently addressable microelectrode array is integrated onto a printed circuit board (PCB) containing associated circuitry for electrode switching and readout. MCF-7 cells were dispensed onto the chip surface and EIS measurements were recorded before and after the cell dispensation. On an average 20% increase in impedance was found associated with cell occupancy on the electrode surface. A positive correlation was observed between cell detection with optical microscopy and with electrical scanning.